Potential target within the tumor microenvironment - MT1-MMP - Liu, Jinlong; Li, Yijing; Lian, Xueqi; Zhang, Chenglin; Feng, Jianing; Tao, Hongfei; Wang, Zhimin (Frontiers in Immunology, 2025)
Matrix metalloproteinases are integral to the modification of the tumor microenvironment and facilitate tumor progression by degrading the extracellular matrix, releasing cytokines, and influencing the recruitment of immune cells. Among the matrix metalloproteinases, membrane-type matrix metalloproteinase 1 (MT1-MMP/MMP14) is the first identified membrane-type MMP and acts as an essential proteolytic enzyme that enables tumor infiltration and metastatic progression. Given the pivotal role of MT1-MMP in tumor progression and the correlation between its overexpression in tumors and unfavorable prognoses across multiple cancer types, a comprehensive understanding of the potential functional mechanisms of MT1-MMP is essential. This knowledge will aid in the advancement of diverse anti-tumor therapies aimed at targeting MT1-MMP. Although contemporary research has highlighted the considerable potential of MT1-MMP in targeted cancer therapy, studies pertaining to its application in cell therapy remain relatively limited. In this review, we delineate the structural characteristics and regulatory mechanisms of MT1-MMP expression, as well as its biological significance in tumorigenesis. Finally, we discussed the current status and prospects of anti-tumor therapies targeting MT1-MMP.